Pengaruh Aspek Keuangan, Inklusi Keuangan, Kompetensi Kewirausahaan dan Orientasi Pasar Terhadap Kinerja UMKM (Studi Kasus pada UMKM Fashion di Surakarta Tahun 2023) - Fadhila, Rizkya; Amalia, Naili (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Micro, Small and Medium Enterprises (MSMEs) are at the forefront of economic development in Indonesia. In the current era, MSMEs are growing increasingly massively, especially in the fashion sector, where in 2022, MSMEs are increasingly selling imported clothing. The city of Surakarta is an object because the growth of MSMEs in the fashion sector is quite high, reaching 781 new MSMEs in 2023, where the performance of MSMEs is an important discussion to research. This research aims to analyze the influence of financial aspects, financial inclusion, entrepreneurial competence and market orientation on the performance of MSMEs. The population in this study was 1,049 MSMEs in the fashion sector with 100 samples taken using a simple random sampling technique. The data collection technique uses a questionnaire. Data analysis techniques use validity tests, reliability tests, classical assumption tests, descriptive analysis, multiple linear regression analysis, F test, t test and coefficient of determination test. The results of the analysis stated that all questionnaire items as research instruments were valid and reliable, as well as the classical assumption tests, including the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test, all variables were declared to have passed the classical assumption test. Multiple linear regression analysis obtained the equation Y = 0.958 + 0.090X1 + 0.513X2 + 0.367X3 + 0.124X4 + e, meaning that all regression coefficients are positive, which means that the variables X1 (financial aspect), X2 (financial inclusion), X3 (entrepreneurial competence) and X4 (market orientation) have a positive effect on the performance of MSMEs in the fashion sector in Surakarta. The partial hypothesis test obtained from financial aspects and market orientation does not have a significant effect on the performance of MSMEs in the fashion sector in Surakarta, while financial inclusion and entrepreneurial competence have a significant effect on the performance of MSMEs in the fashion sector in Surakarta. The F test states that the research model for the influence of the independent variable on the dependent variable is appropriate. The coefficient of determination test shows that financial aspects, financial inclusion, entrepreneurial competence and market orientation are able to explain the performance of MSMEs by 58.9%.